2019
DOI: 10.1002/adsc.201901187
|View full text |Cite|
|
Sign up to set email alerts
|

Trimethoxyphenyl (TMP) as a Useful Auxiliary for in situ Formation and Reaction of Aryl(TMP)iodonium Salts: Synthesis of Diaryl Ethers

Abstract: Herein, we describe a synthetic approach for arylation that exploits the in situ formation and reaction of an unsymmetrical diaryliodonium salt. In this way, aryl iodides are used as reagents in a metal-free reaction with phenols, and a trimethoxyphenyl (TMP) group is used as a "dummy" group to facilitate transfer of a wide range of aryl moieties. The scope of aryl electrophiles and phenol nucleophiles is broad (> 30 examples) and the yields are high (52-95%, 80% avg.). One-pot coupling reactions avoid the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Diaryliodonium salts are air-and moisture-stable, non-toxic, easy to handle and commercially available or easy to prepare [1][2][3][4][5][6][7][8]. During the last decade, noteworthy improvement in the synthesis and use of diaryliodonium salts has been reported [9][10][11][12][13][14][15][16][17][18][19][20][21]. Owing to their electron-deficient nature at the iodine center and to the excellent leaving-group ability of the iodoarene, diaryliodonium salts are frequently employed as aromatic electrophiles in aryl transfer processes [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Diaryliodonium salts are air-and moisture-stable, non-toxic, easy to handle and commercially available or easy to prepare [1][2][3][4][5][6][7][8]. During the last decade, noteworthy improvement in the synthesis and use of diaryliodonium salts has been reported [9][10][11][12][13][14][15][16][17][18][19][20][21]. Owing to their electron-deficient nature at the iodine center and to the excellent leaving-group ability of the iodoarene, diaryliodonium salts are frequently employed as aromatic electrophiles in aryl transfer processes [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…A similar strategy has been used in previous syntheses of ELQ-300 with symmetrical diaryliodonium salts. , In our case, we considered the use of an unsymmetrical diaryliodonium salt in which a relatively inexpensive aryl auxiliary replaces half of the desired aryl group, which would otherwise go to the waste stream, in the coupling with an appropriate phenol. Aryl­(TMP)­iodonium salts (TMP = 2,4,6-trimethoxyphenyl) were a logical choice given their established chemoselective aryl transfer, scalable synthesis, and use in C–O coupling, and the low cost of the auxiliary precursor, 1,3,5-trimethoxybenzene. Moreover, process safety for the synthesis of aryl­(TMP)­iodonium salts has been evaluated, including thermal stability of intermediates, and the synthesis was deemed safe within the operating temperature window .…”
Section: Resultsmentioning
confidence: 99%
“…This chemoselectivity trend has been further applied by other researchers to transfer the electron-poor aryl group of unsymmetrical iodonium salts, and it was noted that the TMP group serves as an improved dummy ligand for aryl transfer processes from heteroaryl(TMP)iodonium salts (Seidl et al, 2016;Dohi et al, 2017). In 2020, Stuart et al reported a convenient method for phenol arylation using the in-situ-generated aryl(TMP)iodonium salts 34 (Gallagher et al, 2020) (Figure 2A, Equation b). Thus, in metal-free reactions, nucleophiles would preferentially react with the more electron-deficient aromatic ring out of the two aryl moieties in unsymmetrical diaryliodonium salts.…”
Section: Heteroaryliodonium Salts As Highly Reactive Pseudo-halidesmentioning
confidence: 91%